Hypocalcemia in Patient Presenting with Preeclampsia at Tertiary Care Hospital - Dr. Ana Mehreen Rajput, Dr. Shagufta Ismail, Dr. Sana Khan, Dr. Najm Us Sehar, Dr. Nusrat Shah, Dr. Ume-Farwa (Drugs and Cell Therapies in Hematology, 2021)
Pre-eclampsia is a pregnancy-associated complication categorized by hypertension and signs of damage to many organs including the liver and kidneys. The objective of the current research was to evaluate the association between hypocalcemia and pre-eclampsia in high-risk women. For this purpose, aprospective, cohort study wasperformed in the department of Obstetrics and Gynecology, Civil Hospital, Karachi fromAugust 03, 2017, to January 02, 2018. In this study, 60 women with a singleton pregnancy of age 18-40 years, with gestational age 35.51 ± 2.86 weeks, were included and distributed into two groups, exposed group included the women with pre-eclampsia while the unexposed group included the normotensive women. Patients with multiple pregnancies, chronic hypertension, diabetes mellitus, twin pregnancy, andkidney and heart disease, were excluded. From all patients, blood samples wereobtained from antecubital vein under aseptic conditions and serum calcium level was measured colorimetrically. The outcome variable, i.e. hypocalcemia (present/absent) was detected in allsamples and results showed that the serum calcium levels were lower significantly in exposed group (5328.73 ± 2638.70 ng/ml)as compared to that of unexposed group (8630.03 ± 1099.26 ng/ml). Additionally, the frequency of hypocalcemia in exposed group was 6-times higher (83.33%) than in unexposed group (13.33%) with p-value of 0.0001 and relative risk of 6.25. It was concluded that the frequency of hypocalcemia in preeclamptic women was very high and there was a direct positive association between hypocalcemia and pre-eclampsia.